A case for promoting negative emission technologies: learning from renewable energy support - Leonie P. Meissner (Carbon Management)
To achieve net-zero emissions by mid-century, the removal of carbon dioxide from the atmosphere through negative emission technologies (NETs) will play an integral part. With renewable energy technologies (RETs), there has already been the introduction and expansion of a clean technology that faced similar obstacles as NETs—high up-front costs, limited competitiveness, and low public perception. This article compares NET policy proposals with the lessons learned from RET support. For NETs, the use of R&D support for innovation is unequivocal due to its nascency, yet the demand-pull instrument differs whether NETs are used as an alternative mitigation strategy, as a bridging technology or as a last resort. As an alternative mitigation method, a market-based approach by integrating NETs into emission trading systems is applicable because the use of NETs has no additional environmental benefit compared to abatement. Using NETs as a bridging technology requires restricting the demand for NETs to control the volume, and possibly type of NETs. This can be achieved via mandates or auctions. As a last resort, the removal via NETs requires heavy state involvement as emission removal constitutes a pure public good. This warrants public procurement or even state-led NET operation.